2014
DOI: 10.2337/db13-1577
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JNK Phosphorylation by a Novel Curcumin Analog Prevents High Glucose–Induced Inflammation and Apoptosis in Cardiomyocytes and the Development of Diabetic Cardiomyopathy

Abstract: Hyperglycemia-induced inflammation and apoptosis have important roles in the pathogenesis of diabetic cardiomyopathy. We recently found that a novel curcumin derivative, C66, is able to reduce the high glucose (HG)-induced inflammatory response. This study was designed to investigate the protective effects on diabetic cardiomyopathy and its underlying mechanisms. Pretreatment with C66 significantly reduced HG-induced overexpression of inflammatory cytokines via inactivation of nuclear factor-κB in both H9c2 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
133
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 41 publications
4
133
0
1
Order By: Relevance
“…Importantly, a recent clinical trial demonstrated that curcumin intervention in pre-diabetic human subjects lowered the number of individuals who eventually progressed to T2D [18] . Numerous in vitro investigations [17,[20][21][22][23][24][25][26] . For example, Pan et al investigated the protective effects of the curcumin derivative C66 on diabetic cardiomyopathy.…”
Section: Dietary Polyphenol and Dietary Polyphenol Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a recent clinical trial demonstrated that curcumin intervention in pre-diabetic human subjects lowered the number of individuals who eventually progressed to T2D [18] . Numerous in vitro investigations [17,[20][21][22][23][24][25][26] . For example, Pan et al investigated the protective effects of the curcumin derivative C66 on diabetic cardiomyopathy.…”
Section: Dietary Polyphenol and Dietary Polyphenol Interventionmentioning
confidence: 99%
“…In the H9c2 cell line (a cardiomyocyte model) and in rat neonatal cardiomyocytes, C66 pretreatment reduced high glucose-induced overexpression of the inflammatory cytokines, possibly via the inactivation of nuclear factor-κB (NF-κB) and the inhibition of Jun NH 2 -terminal kinase (JNK) phosphorylation. In mice with type 1 diabetes, C66 administration decreased the levels of plasma and cardiac tumor necrosis factor-α (TNFα), which is associated with a decreased risk of cardiac cell death [22] . Weisberg et al assessed the effect of native curcumin intervention in HFD fed C57BL/6J mice and the leptin-deficient (ob/ob) obesity mouse model.…”
Section: Dietary Polyphenol and Dietary Polyphenol Interventionmentioning
confidence: 99%
“…Increased cardiomyocyte apoptosis was a predominant cause of loss of contractile tissue, cardiac remodeling and, eventually, dysfunction [8]. Our previous study showed that inhibition of cardiomyocyte apoptosis improved cardiac function in diabetic mice [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that sustained activation of the NF-кB signaling pathway initiated apoptosis in HG-cultured cardiomyocytes [8, 10] and inhibition of this pathway improved cardiac dysfunction in diabetic mice [8]. Thus, targeted inhibition of persistent NF-κB signaling activation might effectively treat DCM.…”
Section: Introductionmentioning
confidence: 99%
“…Compound C66, a JNK inhibitor, was synthesized and purified (>98.4%) as described in our previous studies515253. PF00915275 and C66 were dissolved in DMSO for in vitro experiments and in CMC-Na (1%) for in vivo experiments.…”
Section: Methodsmentioning
confidence: 99%